Experienced disrespect & abuse during childbirth and associated birth characteristics: a cross-sectional survey in the Netherlands - Denise R. Leijerzapf; Marit S. G. van der Pijl; Martine H. Hollander; Elselijn Kingma; Ank de Jonge; Corine J. M. Verhoeven (BMC Pregnancy and Childbirth, 2024)
Abstract Background Experiencing upsetting disrespect and abuse (D&A) during labour and birth negatively affects women’s birth experiences. Knowing in what circumstances of birth women experience upsetting situations of D&A can create general awareness and help healthcare providers judge the need for extra attention in their care to help reduce these experiences. However, little is known about how different birth characteristics relate to the experience of D&A. Previous studies showed differences in birth experiences and experienced D&A between primiparous and multiparous women. This study explores, stratified for parity, (1) how often D&A are experienced in the Netherlands and are considered upsetting, and (2) which birth characteristics are associated with these upsetting experiences of D&A. Methods For this cross-sectional study, an online questionnaire was set up and disseminated among women over 16 years of age who gave birth in the Netherlands between 2015 and 2020. D&A was divided into seven categories: emotional pressure, unfriendly behaviour/verbal abuse, use of force/physical violence, communication issues, lack of support, lack of consent and discrimination. Stratified for parity, univariable and multivariable logistic regression analyses were performed to examine which birth characteristics were associated with the upsetting experiences of different categories of D&A. Results Of all 11,520 women included in this study, 45.1% of primiparous and 27.0% of multiparous women reported at least one upsetting experience of D&A. Lack of consent was reported most frequently, followed by communication issues. For both primiparous and multiparous women, especially transfer from midwife-led to obstetrician-led care, giving birth in a hospital, assisted vaginal birth, and unplanned cesarean section were important factors that increased the odds of experiencing upsetting situations of D&A. Among primiparous women, the use of medical pain relief was also associated with upsetting experiences of D&A. Conclusion A significant number of women experience upsetting disrespectful and abusive care during birth, particularly when medical interventions are needed after the onset of labour, when care is transferred during birth, and when birth takes place in a hospital. This study emphasizes the need for improving quality of verbal and non-verbal communication, support and adequate decision-making and consent procedures, especially before, during, and after the situations of birth that are associated with D&A.